Linking business ecosystem and natural ecosystem together: A sustainable pathway for future industrialization - Yongjiang Shi; Chao Lu; Hong Hou; Lu Zhen; Jialun Hu (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
China has emerged as the second largest economy in the world during the globalization in the last forty years. However, in the last decade, Chinese manufacturing has also demonstrated its dark side causing wide range of concerns globally and directly jeopardize people's health because of serious pollutions. How could the world keep its industrialization yet without damages to the natural environment? The paper proposes a new framework entitled "IE3" by integrating three domains of knowledge-Industrial Entrepreneurship, Industrial Engineering and Industrial Ecology. The IE3 model provides a potential answer to the future development pathway for industrialization, changing from pursuit of quantity to quality via considering resources efficiency and ecology efficiency. The novelty of the research lies in incorporating three originally separated theories into a comprehensive system.
Keywords: 650; business ecosystem; industrial ecology; innovation and entrepreneurship